Blank slate: squares and political order of city. Issue 4 (1st October 2016) - Mehan, Asma
Abstract: This paper aims to analyze the square beyond an architectural element in the city, but weaves this blank slate, with its contemporary socio political atmosphere as a new paradigm. As a result, this research investigates the historical, social and political concept of Meydan – a term which has mostly applied for the Iranian and Islamic public squares. This interpretation, suggested the idea of Meydan as the core of the projects in the city, which historically exposed in formalization of power relations and religious ideologies. In this sense, studying the spatial transformation of Iranian public squares introduces the framework, which is adaptable to contemporary urban context.